Prevalence of Potentially Pathogenic Antibiotic-Resistant Aeromonas spp. in Treated Urban Wastewater Effluents versus Recipient Riverine Populations: a 3-Year Comparative Study - Skwor, Troy (Appl Environ Microbiol, 2020)
Antibiotic resistance continues to be an emerging threat both in clinical and environmental settings. Among the many causes, the impact of postchlorinated human wastewater on antibiotic resistance has not been well studied. Our study compared antibiotic susceptibility among Aeromonas spp. in postchlorinated effluents to that of the recipient riverine populations for three consecutive years against 12 antibiotics. Aeromonas veronii and Aeromonas hydrophila predominated among both aquatic environments, although greater species diversity was evident in treated wastewater. Overall, treated wastewater contained a higher prevalence of nalidixic acid-, trimethoprim-sulfamethoxazole (SXT)-, and tetracycline-resistant isolates, as well as multidrug-resistant (MDR) isolates compared to upstream surface water. After selecting for tetracycline-resistant strains, 34.8% of wastewater isolates compared to 8.3% of surface water isolates were multidrug resistant, with nalidixic acid, streptomycin, and SXT being the most common. Among tetracycline-resistant isolates, efflux pump genes tetE and tetA were the most prevalent, though stronger resistance correlated with tetA. Over 50% of river and treated wastewater isolates exhibited cytotoxicity that was significantly correlated with serine protease activity, suggesting many MDR strains from effluent have the potential to be pathogenic. These findings highlight that conventionally treated wastewater remains a reservoir of resistant, potentially pathogenic bacterial populations being introduced into aquatic systems that could pose a threat to both the environment and public health. IMPORTANCE Aeromonads are Gram-negative, asporogenous rod-shaped bacteria that are autochthonous in fresh and brackish waters. Their pathogenic nature in poikilotherms and mammals, including humans, pose serious environmental and public health concerns especially with rising levels of antibiotic resistance. Wastewater treatment facilities serve as major reservoirs for the dissemination of antibiotic resistance genes (ARGs) and resistant bacterial populations and are, thus, a potential major contributor to resistant populations in aquatic ecosystems. However, few longitudinal studies exist analyzing resistance among human wastewater effluents and their recipient aquatic environments. In this study, considering their ubiquitous nature in aquatic environments, we used Aeromonas spp. as bacterial indicators of environmental antimicrobial resistance, comparing it to that in postchlorinated wastewater effluents over 3 years. Furthermore, we assessed the potential of these resistant populations to be pathogenic, thus elaborating on their potential public health threat.